Global Mindset, Competitive Strategies and Subsidiary Performance of Chinese MNEs: A Dynamic Managerial Capabilities Perspective - Zhang, Shucheng (Curtin University, 2023)
Through the perspective of subsidiary managers’ dynamic managerial capabilities, this research theoretically and empirically finds that subsidiary managers’ global mindset improves subsidiary performance through subsidiary’s competitive response. Such mediation link is further enhanced by three underpinnings of dynamic managerial capabilities, which include perceptual and problem-solving capabilities in managerial cognition, managerial ties with managers of other firms and with local government officials in managerial social capital, and subsidiary and headquarter experience in managerial human capital.